2016
DOI: 10.1016/j.bandl.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Matching heard and seen speech: An ERP study of audiovisual word recognition

Abstract: Seeing articulatory gestures while listening to speech-in-noise (SIN) significantly improves speech understanding. However, the degree of this improvement varies greatly among individuals. We examined a relationship between two distinct stages of visual articulatory processing and the SIN accuracy by combining a cross-modal repetition priming task with ERP recordings. Participants first heard a word referring to a common object (e.g., pumpkin) and then decided whether the subsequently presented visual silent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…In a cross‐modal repetition paradigm, Kaganovich, Schumaker, and Rowland () observed that the N400 is sensitive to the match between auditory and visual speech cues. In their study, participants received auditory‐only words followed by visual‐only words that either matched the initial auditory‐only words or not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a cross‐modal repetition paradigm, Kaganovich, Schumaker, and Rowland () observed that the N400 is sensitive to the match between auditory and visual speech cues. In their study, participants received auditory‐only words followed by visual‐only words that either matched the initial auditory‐only words or not.…”
Section: Discussionmentioning
confidence: 99%
“…Kaganovich et al. () asked their participants to determine whether the visual‐only word matched the word they had heard just before. This is different from the implicit processing of ongoing speech without any mismatch as performed by our participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that deficits in AV processing have been associated with complex neurodevelopmental disorders such as autism spectrum disorders (ASD) and specific language impairment (SLI; e.g., Bebko et al, 2006;Foss-Feig et al, 2010;Iarocci et al, 2010;Irwin et al, 2011;Kaganovich et al, 2014Kaganovich et al, , 2016Smith and Bennetto, 2007), better understanding of the neural bases for typical and atypical AV speech perception will be useful for identifying potential biomarkers that could indicate communication disorders.…”
Section: Introductionmentioning
confidence: 99%